The association between subclinical atherosclerosis in carotid arteries and Connexin 37 gene polymorphism (1019C>T; Pro319Ser) in women - Pitha, J; Hubácek, J A; Cífková, R; Skodová, Z; Stávek, P; Lánská, V; Kovár, J; Poledne, R (International angiology, 2011)
AIM: The aim of our study was to evaluate a possible association between subclinical atherosclerosis in carotid arteries and the connexin 37 gene polymorphism (1019C>T; Pro319Ser) in a population of urban and rural women. METHODS: A 5% population sample of urban women aged 45-54 years (N.=896) and a 1% representative sample of rural women aged 33-72 years (N.=152) were examined using an identical protocol and genotyped for Cx37 gene polymorphism. The association between the Cx37 polymorphism and intima-media thickness in common carotid arteries measured by ultrasound (CIMT) was studied. RESULTS: We have found a different pattern of the effect of the Cx37 gene on CIMT with regard to fasting glycemia with significant interaction between fasting glycemia and Cx37 gene on CIMT (test for equality of slopes P<0.0001). In addition, we also detected potential threshold effect of fasting glycemia at the concentration of 5.5 mmol/L (ANCOVA; P=0.026). Carriers of TT genotype showed protection against subclinical atherosclerosis if their fasting glycemia was above 5.5 mmol/L. CONCLUSION: In women with higher fasting glycemia TT genotype of Cx37 polymorphism was protective against subclinical atherosclerosis. Therefore, the Cx37 gene may exert completely different effects in the artery wall, depending on glycemia.
Keywords: dospělí; protein alfa 4 mezerového spoje; Chi-Square Distribution; hodnocení rizik; arteriae carotides; nemoci arterie carotis; Female; Phenotype; Urban Population; ultrasonografie; Adult; asymptomatické nemoci; ženské pohlaví; průřezové studie; jednonukleotidový polymorfismus; Gene Frequency; lidé; Blood Glucose; Polymorphism, Single Nucleotide; Ultrasonography; genetická predispozice k nemoci; Risk Assessment; Genetic Predisposition to Disease; frekvence genu; Risk Factors; omezení příjmu potravy; Sex Factors; Cross-Sectional Studies; venkovské obyvatelstvo; Carotid Arteries; Aged; sexuální faktory; Czech Republic; Carotid Artery Diseases; městské obyvatelstvo; rizikové faktory; rozdělení chí kvadrát; Česká republika; lidé středního věku; Asymptomatic Diseases; Gap Junction alpha-4 Protein; senioři; konexiny; fenotyp; Fasting; krevní glukóza; Middle Aged; Rural Population; Connexins; Humans